Lymph Vessels Associate with Cancer Stem Cells from Initiation to Malignant Stages of Squamous Cell Carcinoma - Cazzola, Anna; Calzón Lozano, David; Hirsch Menne, Dennis; Dávila Pedrera, Raquel; Liu, Jingcheng; Peña Jimenez, Daniel; Fontenete, Silvia; Halin, Cornelia; Pérez Moreno, Mirna (My University, 2023)
Abstract: Tumor-associated lymph vessels and lymph node involvement are critical staging criteria in several cancers. In skin squamous cell carcinoma, lymph vessels play a role in cancer development and metastatic spread. However, their relationship with the cancer stem cell niche at early tumor stages remains unclear. To address this gap, we studied the lymph vessel localization at the cancer stem cell niche and observed an association from benign skin lesions to malignant stages of skin squamous cell carcinoma. By co-culturing lymphatic endothelial cells with cancer cell lines representing the initiation and promotion stages, and conducting RNA profiling, we observed a reciprocal induction of cell adhesion, immunity regulation, and vessel remodeling genes, suggesting dynamic interactions between lymphatic and cancer cells. Additionally, imaging analyses of the cultured cells revealed the establishment of heterotypic contacts between cancer cells and lymph endothelial cells, potentially contributing to the observed distribution and maintenance at the cancer stem cell niche, inducing downstream cellular responses. Our data provide evidence for an association of lymph vessels from the early stages of skin squamous cell carcinoma development, opening new avenues for better comprehending their involvement in cancer progression. Keywords: cancer stem cells; lymph vessels; skin squamous cell carcinoma; tumor microenvironment